The role of pyroptosis in incomplete immune reconstitution among people living with HIV：Potential therapeutic targets - Chao Xia; Xue Zhang; Vijay Harypursat; Jing Ouyang; Yaokai Chen (Elsevier, 2023)
Globally, HIV infection causes significant morbidity and mortality, and is a major public health problem. Despite the fact that widespread use of antiretroviral therapy (ART) has substantially altered the natural history of HIV infection from originally being a universally lethal disease to now being a chronic medical condition for those taking appropriate treatment, approximately 10-40% of people living with HIV (PLWH) who take effective ART and maintain long-term viral suppression fail to achieve normalization of CD4 + T-cell counts. This phenomenon is referred to as incomplete immune reconstitution or immunological non-response. Although the precise mechanisms underlying this outcome have not been elucidated, recent evidence indicates that excessive pyroptosis may play a crucial role in the development of incomplete immune reconstitution. Pyroptosis is characterized by the formation of pores in the cell membrane, cell rupture, and secretion of intracellular contents and pro-inflammatory cytokines, including IL-1β and IL-18. This excessive inflammation-induced programmed cell death leads to a massive loss of CD4 + T-cells, and inflammatory consequences that may promote and sustain incomplete immune reconstitution. Herein, we review the possible pathways activated in HIV infection by inflammasomes that act as switches of pyroptosis, and the role of pyroptosis in HIV, as well as the relevance of CD4 + T-cells in incomplete immune reconstitution. We also highlight the possible mechanisms of pyroptosis involved in incomplete immune reconstitution, thus paving the way for the development of potential targets for the treatment of incomplete immune reconstitution.